Perancangan Sistem Kendali Prosthetic Arm Penggerak Motor Servo dan Sensor Flex Berbasis Mikrokontroler - Udink Aulia; Syahriza Syahriza; M. Rival Abizar (Jurnal Teknik Mesin Unsyiah, 2020)
This study examines about Prosthetic robotics technology which gradually continue to develop so that its use is wider. In this research author designed a control system on Microcontroller to move Prosthetic Arm. Prosthetic is an artificial device to replace the missing part of the body, this condition can occur through the condition at birth (abnormalities), illness and trauma. The purpose of this research is to create a Prosthetic Arm Prototype that can perform motion gripping, squeezing and removing. Prosthetic Arm was designed by using several control systems such as NANO Arduino, servo motor, flex sensor and Bluetooth as the main component. The Prosthetic Arm movement can only be operated based on the input of the control system that has been designed so that the movement operating on the Prosthetic Arm is desired. The result of this study shows that Prosthetic Arms can do gripping motion at 155° – 173° servo degree, squeezing motion at 180° servo degree and removing motion at 0° servo degree.